Encyclopedia of Life Sciences 2012
DOI: 10.1002/9780470015902.a0002016.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast Genome

Abstract: Chloroplasts contain a genome that is a relic of the endosymbiont that gave rise to the organelle. These genomes typically contain 100–200 genes and encode proteins important for photosynthesis and other chloroplast functions, although dinoflagellate algae have a greatly reduced and fragmented chloroplast genome. Many nonphotosynthetic taxa retain a remnant chloroplast genome. In some organisms the chloroplast genome may be retained to allow redox‐mediated control of gene expression, whereas in others it may c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The cp has an independent semi-autonomous extranuclear genome [ 9 ]. The cp genome is the crucial genetic material of plants, encoding 100–200 essential genes which encode proteins involved in photosynthesis and other chloroplast functions [ 10 ]. Moreover, the cp genomes are ideal tools for studying evolutionary relationships between species because cp genomes are very conserved, and their heredity is independent of the nucleus [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cp has an independent semi-autonomous extranuclear genome [ 9 ]. The cp genome is the crucial genetic material of plants, encoding 100–200 essential genes which encode proteins involved in photosynthesis and other chloroplast functions [ 10 ]. Moreover, the cp genomes are ideal tools for studying evolutionary relationships between species because cp genomes are very conserved, and their heredity is independent of the nucleus [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The chloroplast genome is a closed cyclic structure that consists of large single copy (LSC), small single copy (SSC), and two reverse repeats (IR); its genome size ranges from 100 kb to 200 kb. Protein-coding genes are important in photosynthesis and other functions of the chloroplast and are further divided into nine categories: Photosystem I, cytochrome b6-f complex, Photosystem II, ATP synthase, ribulose bis-phosphate carboxylase, ribosome large subunit, ribosome small subunit, RNA polymerase, and a hypothetical protein [ 11 ]. The overall structure and genome of the chloroplast are relatively conserved, although in-depth studies in chloroplast genomics and biology have identified several mutations and small structural changes among various species including insertions, deletions, reversals, and translocations [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The chloroplast genome is a relic of a endosymbiont that that was integrated into the cell and utilized as an organelle; it typically contains 100-200 genes and encodes proteins involved in photosynthesis and other chloroplast functions (Howe 2012). Chloroplast-to-nucleus retrograde signaling is triggered through pathways such as the Mg-ProtoIX dependent pathway and the plastid gene expression-dependent pathway (Nott et al 2006).…”
Section: Introductionmentioning
confidence: 99%